mRNAs coding for A1 and A2 isoforms of translation factor eEF1A demonstrate different half-lives while A1 and A2 proteins are similarly stable in MCF7 cells - Vislovukh, A.A.; Gralievska, N.L.; Naumovets, M.G.; Negrutskii, B.S.; El'skaya, A.V. (Вiopolymers and Cell, 2013)
Eukaryotic translation elongation factor 1A (eEF1A) exists as two 98 % homologous isoforms eEF1A1 and eEF1A2 that are tissue/development specific and differentially linked to apoptosis/cancerogenesis. A2 is overexpressed in a number of tumors while unusual expression of A1 is observed in injured muscles. To approach a possible mechanism underlying induced changes in the relative amounts of the isoforms we examined the intrinsic stability of the proteins and their mRNAs in human cancer cells. Aim. To estimate half-life of the isoforms of eEF1A at mRNA and protein level in human cancer cells. Methods. To measure mRNA stability the transcriptional block technique was applied, with subsequent analysis of the mRNA level by qPCR. To determine the protein decay rate the translation was blocked by cycloheximide and changes in the protein level were detected by Western blot. Results. Calculation of the protein stability revealed half-life of 72 for eEF1A1 and 95 hours for eEF1A2. Half-life of EEF1A1 and EEF1A2 mRNAs were 3 and 60 hours respectively. Conclusions. Despite similar protein stability, the isoforms of eEF1A dramatically differ in the half-lives of their mRNAs, suggesting that the mRNA decay mechanism is one of the main regulators of eEF1A1/A2 amount in MCF7 cancer cells. Евкаріотний фактор елонгації трансляції (eEF1A) існує у вигляді двох гомологічних на 98 % ізоформ eEF1A1 і eEF1A2, які є тканиноспецифічними, відрізняються за представленістю в онтогенезі та по-різному пов’язані з апоптозом і канцерогенезом. Згідно з попередніми даними, eEF1A2 має підвищений рівень експресії у деяких пухлинах, а eEF1A1 – у пошкоджених м’язах. Щоб зрозуміти механізм, за яким змінюється відносна кількість ізоформ, ми дослідили стабільність білків та їхніх мРНК у клітинах раку людини. Мета. Оцінити час напівжиття ізоформ eEF1A на рівні мРНК і білка в клітинах раку людини. Методи. Для вимірювання стабільності мРНК використано техніку блокування транскрипції з подальшим аналізом рівня мРНК із застосуванням кількісної ПЛР. Для визначення швидкості розпаду білка трансляцію блокували циклогексимідом, подальші зміни рівня білка виявляли методом Вестерн-блоту. Результати. За підрахунками, стабільність білка зберігалася протягом 72 год у разі eEF1A1 та 95 год – у разі eEF1A2. Значення часу напівжиття EEF1A1 і EEF1A2 мРНК становлять відповідно 3 і 60 год. Висновки. Незважаючи на подібні значення стабільності білка, ізоформи eEF1A значно відрізняються за часом напівжиття їхніх мРНК, внаслідок чого можна припустити, що контроль стабільності мРНК є одним з основних механізмів регуляції експресії eEF1A1/ A2 в клітинах раку молочної залози MCF7. Эукариотический фактор элонгации трансляции (eEF1A) существует в виде двух гомологичных на 98 % изоформ eEF1A1 и eEF1A2, являющихся тканеспецифическими, отличающихся представленностью в онтогенезе и по-разному связанных с апоптозом и канцерогенезом. Согласно наблюдениям, eEF1A2 имеет повышенный уровень экспрессии в некоторых опухолях, а eEF1A1 – в поврежденных мышцах. Чтобы понять механизм, по которому изменяется относительное количество изоформ, мы исследовали стабильность белков и их мРНК в клетках рака человека. Цель. Оценить время полужизни изоформ eEF1A на уровне мРНК и белка в клетках рака человека. Методы. Для измерения стабильности мРНК использовали технику блокирования транскрипции с последующим анализом уровня мРНК с применением количественной ПЦР. Для определения скорости распада белка трансляцию блокировали циклогексимидом, дальнейшие изменения уровня белка выявляли методом Вестерн-блота. Результаты. По расчетам, стабильность белка сохранялась в течение 72 ч в случае eEF1A1 и 95 ч – в случае eEF1A2. Время полужизни EEF1A1 и EEF1A2 мРНК составляло соответственно 3 и 60 ч. Выводы. Несмотря на подобные значения стабильности белка, изоформы eEF1A значительно отличаются по времени полужизни их мРНК, вследствие чего можно предположить, что контроль стабильности мРНК является одним из основных механизмов регуляции экспрессии eEF1A1/A2 в клетках рака молочной железы MCF7.